Development of a functional model of nursing care in cancer - Alarcón, Angela Maria; Barrera Ortiz, Lucy; Carreño, Sonia Patricia; Carrillo, Gloria Mabel; Farías, Ruth Elena; González, Gladys; Sánchez Herrera, Beatriz; Santamaría, Narda (Investigación y Educación en Enfermería, 2014)
Objective. To propose and validate a functional model that permits addressing, guiding, and qualifying nursing care in the Colombian National Cancer Institute. Methodology. Within the framework of the teaching-service work and as response to the priorities established by the National Cancer Institute, the need to have a model was determined to better understand the nursing work in the institution. For this purpose a study was conducted in three phases: 1) Analysis of the context, 2) Elaboration and analysis of the narratives of care, and 3) Development of the Functional Model of Nursing Care from the narratives. Results. Based on the analysis of the context, we selected the theory of “Nursing as Caring” by Boykin and Schoenhofer and, as of such; a guide was developed and applied for the construction and analysis of the narratives of care. Lastly, through an analysis of the content of the narratives of care 143 nominal codes emerged along with eight central categories or concepts. The way these concepts are related in the content of the text gave way to the assumptions of the National Cancer Institute’s model of nursing care whose dynamic was defined and diagramed for communication. Validation of the Model of Nursing Care ratified the positions expressed by the participants. Conclusion. Development of a sequential dynamics of contextual analysis, space and expression of a reflexive nursing practice and analysis of the contents of some narratives of nursing care product of such, permitted proposing and validating the National Cancer Institute’s Model of Nursing Care that addresses, transmits, guides, and qualifies professional performance in the institution.